Efficacy and costs of handheld sprayers in the subhumid savanna for cogongrass control - Nielsen, O.K.; Chikoye, David; Streibig, J.C. (Cambridge University Press, 2005)
Cogongrass continues to be one of the most invasive weeds in the subhumid savanna. Herbicide application expenses depend on equipment costs, costs of water transport for spraying, and chemical costs. In three on-farm experiments on land heavily infested with cogongrass, the effectiveness of a knapsack sprayer (KS), a very low volume sprayer (VLV), and a rope wick (RW) applicator was tested at Ijaye, Nigeria, from 2000 to 2001. The sprayers differed in application method, price, and carrier volume required. The dose–response curves for the three applicators were identical in all parameters except at very high doses for the RW. Consequently, there were no apparent differences in glyphosate effectiveness, even when it was applied with different equipment and different carrier volumes. However, even at very high doses, the RW was not as efficient as was the KS and VLV. Actual biomass reduction of cogongrass was greater with the KS and VLV. Even though the KS and VLV generally gave better control levels than the RW, the latter is more user-friendly because it does not require protective masks, which are often unavailable in sub-Saharan Africa. In a situation with labor scarcity, weeding with the RW was cheaper than hand weeding with hoes. The VLV was more economical when used on areas larger than 10 ha than was the RW. The KS was more economical than all other methods when used on areas larger than 2 ha.